Book Reviews (Journal of Finance, 1991)
Book reviewed in this article: Asymmetric Information, Corporate Finance, and Investment . By R. GLENN HUBBARD. Chicago: The University of Chicago Press, 1990. Pp. ix + 343. Japanese Takeovers: The Global Contest for Corporate Control . By W. CARL KESTER. Boston: Harvard Business School Press, 1991. Pp. xxii + 298. Breaking Financial Boundaries: Global Capital, National Deregulation, and Financial Services Firms. By DAVID M. MEERSCHWAM. Boston, MA: Harvard Business School Press, 1991. Pp. ix + 306. The S&L Debacle: Public Policy Lessons for Bank and Thrift Regulation. by LAWRENCE J. WHITE. New York, Oxford: Oxford University Press, 1991. Pp. xiv + 308.